Modeling of the Effect of MgO and ZrO2 on Sintering of Alumina - Al.Mayaly, H. K.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research studyies the effect of MgO and ZrO2 as additives in sintering Al2O3 . The experimental results are modeled using ( L2 _ regression) technique , sintered density and grain size rate measurments were accounted by utilizing experimental results of undoped , MgO doped and ZrO2 doped alumina impregrated with spherical large pores in final stage of sintering . The effect of each additive is inhibitian of the grain growth and increasing the densification rate which enhances the kinietics of densification and the removal of large and small pores.